2022
DOI: 10.3389/fphar.2022.906419
|View full text |Cite
|
Sign up to set email alerts
|

Alterations and Potential Applications of Gut Microbiota in Biological Therapy for Inflammatory Bowel Diseases

Abstract: Inflammatory bowel disease (IBD), including Crohn’s disease and ulcerative colitis, is a chronic immune-mediated inflammatory disorder of the gastrointestinal tract that is closely associated with dysbiosis of the intestinal microbiota. Currently, biologic agents are the mainstream therapies for IBD. With the increasing incidence of IBD, limitations of biologic agents have gradually emerged during treatment. Recent studies have indicated that gut microbiota is highly correlated with the efficacy of biologic ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 154 publications
0
12
0
Order By: Relevance
“…Additionally, the contribution of gut microbiota alteration in the pathogenesis of IBD is generally accepted [ 39 , 40 , 41 ]. PA has been reported to be a significant modifier in preventing and restoring gut dysbiosis [ 42 ]; PA is associated with an increase in microflora diversity, an improvement in the development of commensal bacteria, and a beneficial metabolic function [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the contribution of gut microbiota alteration in the pathogenesis of IBD is generally accepted [ 39 , 40 , 41 ]. PA has been reported to be a significant modifier in preventing and restoring gut dysbiosis [ 42 ]; PA is associated with an increase in microflora diversity, an improvement in the development of commensal bacteria, and a beneficial metabolic function [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The GM is a potential controller of wellness and disease. As demonstrated by experimental, clinical, and epidemiological evidence, a dysbiotic microbiota (i.e., a microbiota that deviates from the “eubiotic” status in terms of diversity and functionality [ 11 ]) is implicated in a range of diseases in adults, including inflammatory bowel disease [ 12 , 13 ], arthritis [ 14 ], cancer [ 15 ], neurological and neuropsychiatric disorders [ 16 ], cardiometabolic [ 17 ] and cardiovascular [ 18 ] disease, obesity [ 19 ], type 2 diabetes [ 20 , 21 , 22 ], and, as detailed below, infertility.…”
Section: Gut Microbiota: a New Player In Townmentioning
confidence: 99%
“…For example, infliximab is a monoclonal antibody which acts as an inhibitor of proinflammatory cytokine TNF-α effectively attenuating its release [86]. Many studies have shown that during the anti-inflammatory treatment, both the gut microbiota and its metabolic product compositions are significantly changed [87]. As for infliximab treatment, in a systemic review of 10 studies, Estevinho et al found the gut microbiome α-diversity of the patients who responded to infliximab have be improved with the increased abundances in genus, including Faecalibacterium, Roseburia, or Clostridium [88].…”
Section: 3mentioning
confidence: 99%
“…In this study, they found that despite the nationality, patients from both populations show an increase in Clostridiales after receiving Infliximab treatment. Apart from Clostridiales, the number of bacteria species such as Bifidobacterium, Clostridium colinum, Eubacterium rectale, and Vibrio also showed an increasing trend after infliximab treatment [87]. More importantly, the increased abundance of Clostridiales can serve as a biomarker for predicting the effectiveness of infliximab treatment with an accuracy of up to 85% [89] During the mild or even severe stages of the disease, patients are recommended to take surgery to remove the infected colon because of the increased risk of colon cancer.…”
Section: 3mentioning
confidence: 99%